Perkawinan Anak di Kabupaten Wajo - Hasana, Fauziatul; Syarif, Nurul Hidayanti; Idrus, Idham Irwansyah (ETHNOGRAPHY: Journal of Design, Social Sciences and Humanistic Studies, 2025)
The phenomenon of child marriage is a social event that must be taken seriously because it greatly affects the lives of adolescents entering adulthood. Wajo Regency is included in the three main areas in South Sulawesi province with a high rate of child marriage under 16 years old with more than 23 cases, namely Bone, Wajo, and Soppeng Regencies. This article aims to find out the causes of child marriage in the Wajo regency area and build awareness of the dangers of child marriage. The method used is a literature study obtained from books and scientific articles that are in accordance with the research theme. Article data is obtained from various journals and Google Scholar databases. The data analysis technique used is content analysis. The findings of this study are that there are four factors that cause the high rate of child marriage in Wajo Regency, first: cultural stigma attached to society such as early matchmaking; second, the discontinuation of children's education; third, the influence of social media on children; and four, the economic problems of parents. So the importance of the role of parents, schools, communities and the government in anticipating the high rate of child marriage